2001
DOI: 10.1007/s003300101130
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastases from head and neck squamous cell carcinoma: MR imaging with ultrasmall superparamagnetic iron oxide particles (Sinerem MR) – results of a phase-III multicenter clinical trial

Abstract: The aim of this study was to compare the clinical usefulness of ultrasmall superparamagnetic iron oxide (USPIO) MR contrast media (Sinerem, Guerbet Laboratories, Aulnay-sous-Bois, France) with precontrast MRI in the diagnosis of metastatic lymph nodes in patients with head and neck squamous cell carcinoma, using histology as gold standard. Eighty-one previously untreated patients were enrolled in a multicenter phase-III clinical trial. All patients had a noncontrast MR, a Sinerem MR, and surgery within a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(84 citation statements)
references
References 23 publications
4
77
1
2
Order By: Relevance
“…Due to this inaccuracy, most surgeons prefer to overtreat patients, performing bilateral radical neck dissections that may result in increased morbidity (9). Accurate presurgical imaging studies are thus needed, in an attempt to select the most appropriate surgical procedure (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to this inaccuracy, most surgeons prefer to overtreat patients, performing bilateral radical neck dissections that may result in increased morbidity (9). Accurate presurgical imaging studies are thus needed, in an attempt to select the most appropriate surgical procedure (23).…”
Section: Discussionmentioning
confidence: 99%
“…USPIO particles have been developed with the knowledge that they are selectively taken by cells of the reticuloendothelial system present in nonmetastatic LN, with differences in enhancement reflecting the functional status of the nodes, allowing discrimination of benign from malignant ones (17,28). Although their use for human studies has been limited (9,10,(15)(16)(17)(18)(19)(20), they have showed encouraging results, with reported high sensitivity and specificity values (9,10,16,17,19,20). Recently, combined positron emission tomography (PET)/CT has been used successfully for staging of nodal disease in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also the introduction of lymph node specific contrast agents like ultrasmall particles iron oxide on magnetic resonance imaging (MRI) provides differentiation between benign and malignant lymph nodes in the head and neck and results are improving [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%